Analysis of unit trust investors behaviour : the case of Saham Amanah Sabah - Ag Ismail Ag Ramle (2017)
The study aimed to investigate the impact of behavioural biases on Saham Amanah Sabah (SAS) investors' financial decision making. SAS is a state government backed unit trust scheme. This research studies the behavioural biases including loss aversion, disposition effect, regret aversion and herding. Empirical data has been collected through the administration of questionnaires. The partial least squares structural equation modelling using SmartPLS version 2.0 was selected to analyse the data. The study concluded that the Loss Aversion, Regret Aversion and Herding biases have direct impact on the investors' decision making meanwhile Disposition Effect does not. As a result, these biases lead the investors of SAS to continue holding their units despite SAS did not perform well. These results are highly consistent with the results of many previous studies. Should the investors were not influenced by these biases and acted rationally, their current investment value or wealth would have been better. This situation may well happen to other state government backed unit trust scheme throughout Malaysia since they share the same similarity which is they have only one product under their umbrella. However the result may not be applied to private owned unit trust fund since they offer various products under their umbrella. This study may benefits state government backed unit trust provider in understanding the behaviour of their unitholders, meanwhile for individual investors, they may be aware of the impact of their behavioural biases towards their investment objective. In long term, hopefully, individual investors will increase their rationality in their investment decision making. Theoretically, this research suggested that behavioural finance theories may well explain the action of SAS unitholders irrational action rather than applying stan9ard finance theories.